In-vivo visualization of the photoreceptors using Spectralis High Magnification Module imaging in central serous chorioretinopathy - Gujar, Ramkailash; Muzi, Alessio; Cagini, Carlo; Mariotti, Cesare; Piccolino, Felice Cardillo; Chhablani, Jay; Lupidi, Marco (American journal of ophthalmology case reports, 2022)
To visualize photoreceptors using the Spectralis High Magnification Module (HMM) in a case of central serous chorioretinopathy (CSCR) and to correlate the findings with those of optical coherence tomography (OCT) and optical coherence tomography angiography (OCT-A). A 35-year-old Caucasian male presenting with chronic CSCR in the left eye was examined using HMM, OCT and OCT-A. The photoreceptors mosaic was assessed both in diseased and apparently uninvolved areas. A partial topographic correlation between the loss of photoreceptors on HMM images and an altered reflectivity of the photoreceptor layer on en-face OCT was noted. Interestingly, a correlation between the photoreceptor damage on HMM and choriocapillaris flow-void areas on OCT-A was seen. HMM is a non-invasive imaging modality, allowing the in-vivo visualization of photoreceptor damage in a diseased retina. A focal abnormal perfusion of the choriocapillaris might influence the integrity of the overlying photoreceptors in CSCR.